Zapisz w najprostszej postaci wyrazenie:
a) -2x -3(1-x)
b) pierwiastek z 2(2-x)-2(x+ pierwiastek z 2)
c)4(n-1)-½(8n+4)
d)5(4x-2)-3(x+4)
e)3(2-x)-(4+x)
f) 4x kwadrat-3x(x-2) +2x
g)(5-x)x+4(x-3)-6x(0,3x+0,5)
h) 3x(x-6y)-2y(x+7y)
bardzo prosze o pomoc

2

Odpowiedzi

2009-12-02T18:38:46+01:00
A) -2x -3(1-x)= -2x-3+3x=x-3
b) √2(2-x)-2(x+ √2)= 2√2-x√2-2x-2√2=-x√2-2√2
c)4(n-1)-½(8n+4)= 4n-4-4n-2=-6
d)5(4x-2)-3(x+4)=20x-10-3x-12=17x-22
e)3(2-x)-(4+x)=6-3x-4-x=2-4x
f) 4x²-3x(x-2) +2x=4x²-3x²+6x=x²+6x
g)(5-x)x+4(x-3)-6x(0,3x+0,5)=5x-x²+4x-12-1,8x²-3x=-2,8x²+6x-12
h) 3x(x-6y)-2y(x+7y)=3x²-18xy-2xy-14y=3x²-20xy-14y






2009-12-02T18:39:03+01:00
A)=-2x-3+3x=x-3
b)=2√2-√2x-2x-2√2=-2x-√2x
c)=4n-4-4n-2=-6
d)=20x-10-3x-12=17x-22
e)=6-3x-4-x=-4x+2
f)=4x²-3x²+6+2x=x²+2x+6
g)=5x-x²+4x-12-1,8x²-3x=-2,8x²+6x-12
h)=3x²-18xy-2xy-14y²=3x²-14y²-20xy